La diagnosi precoce di malattia. Issue 1 (March 2019) - Rossi, Federica; Pieruzzi, Federico
Early diagnosis in Fabry's disease Aderson-Fabry disease is an X-linked, lysosomal, storage disorder characterized by the decreased activity of alpha-Galactosidase A, which results in accumulation of globotriaosylceramide (Gb-3) in cells and tissues throughout the body, leading to a wide spectrum of clinical manifestations. Patients are often misdiagnosed or diagnosed late in their life. This is due to the phenotypic heterogeneity, the poor awareness of this rare disease, and many pitfalls when making a differential diagnosis, in adulthood, as well as in the early stages. Delayed diagnosis has significant clinical implications, because the progression of the disease over time can lead to irreversible end-stage renal disease and life-threatening cardiovascular or cerebrovascular complications. Early diagnosis remains essential in order to start an early treatment and reduce the progression of the disease, thus maximizing the chance to improve patient outcomes. Newborn screening, high-risk patients' identification, and increasing pediatricians' and clinicians' knowledge on this condition, are good strategies to avoid late referrals of Anderson-Fabry patients to reference centers.